The Effect of Glucocorticoids on Bone Mass in Patients with Asthma and Chronic obstructive Pulmonary Disease - Evrim Karadağ Saygı; Demet Ofluoğlu; Feyza Ünlü Özkan; Sait Karakurt (Galenos Yayinevi, 2005)
Inhaled corticosteroids and bronchodilators have become a key element in the maintenance treatment of bronchial asthma and chronic obstructive pulmanory disease (COPD). It is well known that long-term systemic steroid use causes osteoporosis, whereas inhaled corticosteroids and bronchodilators have been discussed to be cause of such side-affect. The aim of this study was to detect the effect of long term inhaled/oral steroids and bronchodilators on bone mineral density (BMD) with asthma and COPD. Fifty-three patients with bronchial asthma (n=44) and COPD (n=9) were enrolled in this study. BMD were measured and risk factors for osteoporosis were detected. BMD measurements of lumbar area of the spine (L2-4), neck of femur and femoral ward's triangle zone were performed by the dual energy x-ray absorptiometer (LUNAR). 53 patients evaluated in three groups according to treatment type; 26 patients were using inhaled corticosteroids and bronchodilators (group 1), 18 patients were using only bronchodilators (group 2) and 9 patients were using (group 3) oral corticosteroids and bronchodilators. There were significant differences between group 3 and other two groups in terms of BMD, T and Z scores of the lumbar and femoral neck (p<0.05). No difference in BMD, T and Z scores was noted between group 1 and group 2 (p>0.05). As a result, we suggest that systemic corticosteroids negatively affect bone mineral density more than inhaled corticosteroids in patients with COPD.